+0

# h(t) = -2t+2 , Find h (-3t)

0
522
3

h(t) = -2t+2 , Find h (-3t)

Guest Aug 27, 2015

#3
+91972
+5

"h" is just the name of the function.  Often f is used but any letter can be used :)

And yes, you just replace the original t with -3t like the 2nd anon did.

h(-3t) = -2(-3t) + 2

h(-3t) = 6t + 2

Melody  Aug 27, 2015
Sort:

#1
0

h(t) = -2t+2 , Find h (-3t)

Assuming I understand you

-3 h t

Guest Aug 27, 2015
#2
+5

I don't know why the first answer contains an 'h'.  What that is saying is that you should plug in '-3t' for each 't' you see in the problem so:  h(-3t) = -2(-3t) + 2

Guest Aug 27, 2015
#3
+91972
+5

"h" is just the name of the function.  Often f is used but any letter can be used :)

And yes, you just replace the original t with -3t like the 2nd anon did.

h(-3t) = -2(-3t) + 2

h(-3t) = 6t + 2

Melody  Aug 27, 2015

### 10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details